2016
DOI: 10.1177/1077546314567181
|View full text |Cite
|
Sign up to set email alerts
|

A numerical solution for fractional optimal control problems via Bernoulli polynomials

Abstract: This paper presents a new numerical method for solving fractional optimal control problems (FOCPs). The fractional derivative in the dynamic system is described in the Caputo sense. The method is based upon Bernoulli polynomials. The operational matrices of fractional Riemann–Liouville integration and multiplication for Bernoulli polynomials are derived. The error upper bound for the operational matrix of the fractional integration is also given. The properties of Bernoulli polynomials are utilized to reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 30 publications
2
77
0
Order By: Relevance
“…Next, in this example, we use the numerical results of linear programming. The exact solution of equation (39) for ¼ 1 is equal to: Keshavarz et al (2015) Number of solution by Tohidi and Nik (2015) Number of solution by Jafari and Tajadodi (2014) Number of solution by Lotfi et al (2011) 0.1 2.39 Â 10 À6 -1.34 Â 10 À5 1.34 Â 10 À5 0.2 1.21 Â 10 À6 6.2315. 10 À8 2.12 Â 10 À5 2.12 Â 10 À5 0.3 1.72 Â 10 À6 -3.24 Â 10 À5 3.24 Â 10 À5 0.4 6.82 Â 10 À7 2.4565.…”
Section: Examplementioning
confidence: 99%
“…Next, in this example, we use the numerical results of linear programming. The exact solution of equation (39) for ¼ 1 is equal to: Keshavarz et al (2015) Number of solution by Tohidi and Nik (2015) Number of solution by Jafari and Tajadodi (2014) Number of solution by Lotfi et al (2011) 0.1 2.39 Â 10 À6 -1.34 Â 10 À5 1.34 Â 10 À5 0.2 1.21 Â 10 À6 6.2315. 10 À8 2.12 Â 10 À5 2.12 Â 10 À5 0.3 1.72 Â 10 À6 -3.24 Â 10 À5 3.24 Â 10 À5 0.4 6.82 Â 10 À7 2.4565.…”
Section: Examplementioning
confidence: 99%
“…It was found that various applications can be modeled with the help of the fractional derivatives [6,7]. For example, the nonlinear oscillation of earthquake [8], the fractional optimal control problems for dynamic systems [9,10,11,12], and the fluid-dynamic models with fractional derivatives can eliminate the deficiency arising from the assumption of continuous traffic flow [13,14,15]. During the last decades, several methods have been used to solve fractional differential equations, fractional partial differential equations, fractional integro-differential equations, the initial and boundary value problems, and dynamic systems containing fractional derivatives, such as Adomian's decomposition method [16,17], fractional-order Legendre functions [18], fractional-order Chebyshev functions of the second kind [19], Homotopy analysis method [20], Bessel functions and spectral methods [21], Legendre and Bernstein polynomials [22], finite element methods [23], Legendre collocation [24], modified spline collocation [25], multiquadratic radial basis functions [26], and other methods [27,28,29,30,31,32,33].…”
Section: Summary Of Fractional Calculus Historymentioning
confidence: 99%
“…Lemma 3 Keshavarz, Ordokhani, and Razzaghi [16] Suppose that f ∈ L 2 [0, 1] is approximated by f N such that…”
Section: Theoremmentioning
confidence: 99%